(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This study dealt with the basics of financial inclusion in terms of concept, importance and objectives, The empowerment of women financially and bank,and then the relationship between financial inclusion and women, and determine the requirements of inclusion Financial resources for women. The analytical descriptive method was used for data, which included reviewing and analyzing information And data in economic and financial literature. The study: reached a number of conclusions, the most important of which are Financial inclusion contributes to women’s financial and banking support, as there is a positive relationship between financial institutions Banking and women’s access to financial and banking services, thus playing a role in stimulating economic growth Through financial institutions. Increasing women’s participation in theeconomy is making gains in GDP (3.5%) to (2%).The most important recommendation is to recognize the importance of women’s financial inclusion and disclosure On this priority by the monetary and financial authorities, and to include this importance within the strategy Which is supported by the efforts of the State.